2020
DOI: 10.1177/2192568219882346
|View full text |Cite
|
Sign up to set email alerts
|

Defining the MIS-TLIF: A Systematic Review of Techniques and Technologies Used by Surgeons Worldwide

Abstract: Study Design: Systematic review. Objective: To date there is no consensus among surgeons as to what defines an MIS-TLIF (transforaminal lumbar interbody fusion using minimally invasive spine surgery) compared to an open or mini-open TLIF. This systematic review aimed to examine the MIS-TLIF techniques reported in the recent body of literature to help provide a definition of what constitutes the MIS-TLIF, based on the consensus of the majority of surgeons. Methods: We created a database of articles published ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 97 publications
0
67
0
1
Order By: Relevance
“…Advantages of the TLIF approach include relatively easier access to the posterior structures, including the lamina, ligamentum flavum, and facet joints 7 . However, Mis-TLIF has demonstrated that it results in less intraoperative blood loss, shorter hospital stay and recovery time, fewer complications, and less need for postoperative narcotic use, with similar clinical outcomes and fusion rates compared with open TLIF [8][9][10][11] . Mis-TLIF remains one of the most popular surgical procedures because of surgeons' familiarity with the posterior approach anatomy 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of the TLIF approach include relatively easier access to the posterior structures, including the lamina, ligamentum flavum, and facet joints 7 . However, Mis-TLIF has demonstrated that it results in less intraoperative blood loss, shorter hospital stay and recovery time, fewer complications, and less need for postoperative narcotic use, with similar clinical outcomes and fusion rates compared with open TLIF [8][9][10][11] . Mis-TLIF remains one of the most popular surgical procedures because of surgeons' familiarity with the posterior approach anatomy 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional open TLIF, MIS-TLIF was believed to have several advantages due to its minimally invasive principles such as minimizing soft tissue damage, performing bilateral decompression through unilateral approach and keeping stabilization of the posterior spinal segment [9]. With the advancement of robotic technology, spine surgeons could perform the operation in a more accurate and precise robot-assisted manner [26].…”
Section: Discussionmentioning
confidence: 99%
“…With the advances in minimally invasive spine surgery, Foley et al introduced minimally invasive TLIF (MIS-TLIF) approach in 2002, which subsequently showed several advantages such as less intraoperative blood loss, shorter recovery time and fewer complications with comparable outcomes [5][6][7][8]. Latest review suggested that 79% of MIS-TLIF publications inserted pedicle screws in a percutaneous approach [9]. Given the indirect visual access of entry point for pedicle screw placement, the risk of screw malposition and perforation may increase in conventional MIS-TLIF procedure [10,11].…”
mentioning
confidence: 99%
“…It is imperative for the accurate placement of tube to minimize soft tissue damages and decrease operative time. Preoperative plans are made for accurate placement of the tubular retractor 36) . Microscope is used for visualization.…”
Section: Instruments and Visualization 1) Retractor Tube Endoscope And Working Instrumentsmentioning
confidence: 99%